Effect of crude extract of menthaspicata on fertility in Albino female mice (Baghdad Science Journal, 2007)
The crude aqueous extract of menthespicata , the objective of this study was to investigate the effects of this extraction , on the histological changes of the ovares and levels of sex hormone , ( FSH , LH , Estradiol ) in albino female mice . the extract was given orally for( 45 ) days . fourty mature female mice were used in this study , the animals divided into four major groups . each group was include ten mice . the first three groups was given different concentration )) (21 , 14 , 7 %) . While the fourth group considered as control group which had been administrated tab water . For ( 45 ) days each group had been killed for hormonal assay in blood , and for histological study . The results showed that aqueous extract of menthe spicata , increased the significant value p 0.05 in both first and second group ( 21 ,14 % ) . The results of histological study for ovaries recorded asignificant increasing in the number of ovarian follicles in different stages , moreover the increasing on follicles diameters and in the size and activity of the ovaries . This result appeared clearly in the third group (7%) . In the seam time the athere two groups ( first , second ) recorded reduced in the number and diameters of ovarian follicles and in the corpus luteum . From the above mentioned outcomes we can conclude that the equeous extract of menthe spicata had a positive effect on the female reproductive systeme when it used in low concentration , while the high concentration had negative effect or toxcic effect .